Backflow-assisted time-resolved phase modulation in nematic liquid crystal Pi-Cells. (December 2022) - Jin, Yihan; Elston, Steve J.; Fells, Julian A.J.; Chen, Bohan; Li, Mengmeng; Kamal, Waqas; Zhao, Zimo; Morris, Stephen M.
Highlights: A new time-resolved characterisation technique was developed and verified to determine the optical phase modulation in liquid crystal (LC) devices. Time-dependent phase modulation behaviour of nematic LCs in different geometries has been determined. The lowest voltage amplitude corresponding to π phase modulation is observed for the nematic pi-cell. Backflow hinders the dynamic phase response of some nematic configurations but not others. Technique can be used to identify the best-performing device configurations. Abstract: By monitoring the time-dependent phase modulation behavior, we demonstrate the benefits of backflow on the phase modulation depth of nematic liquid crystal (LC) pi-cells in comparison to the phase modulation observed for other nematic LC device configurations. Specifically, results are presented for the time-resolved phase modulation of three different nematic LC device configurations under a range of electric field conditions: pi-cell (parallel-rubbed alignment layers), Fréedericksz cell (anti-parallel rubbed alignment layers), and a hybrid aligned nematic (HAN) device. The time-dependent behavior is obtained experimentally with a Michelson interferometer with a piezoelectric scanning mirror in the reference arm, which provides a continuous phase ramp in the reference signal. By recording the interference signal intensity, it is then possible to extract the change in optical phase as a function of time. It is shown that both the pi-cell and Fréedericksz cell exhibit a modulation that is greater than π radians for a double-pass configuration (2π radians for a four-pass configuration), with the lowest voltage amplitude corresponding to π phase modulation being observed for the pi-cell. Through the time-resolved response, it is shown that the presence of backflow hinders the dynamic phase response of the Fréedericksz device but does not negatively impact the behavior of the pi-cell. These results are found to be in good agreement with simulations of the phase modulation for the three nematic devices when backflow is taken into consideration.